2021
DOI: 10.17691/stm2021.13.5.09
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Spinal Fusion Using Lateral Oblique (Pre-psoas) Approach (Review)

Abstract: Lumbar spinal fusion is one of the most common operations in spinal surgery. For its implementation, anterolateral (pre-psoas) approach (oblique lumbar interbody fusion, OLIF) is now increasingly used due to its high efficacy and safety. However, there is still little information on the clinical and radiological results of using this technique. The aim of the study was to analyze the safety and efficacy of OLIF in the treatment of lumbar spine disorders as presented in the literature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
8

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 63 publications
0
5
0
8
Order By: Relevance
“…Some nerve branches supplying the psoas traverse the intervertebral disc obliquely prior to ramification within the muscle and are, therefore, vulnerable to injury when muscle fibers of the superficial layer of psoas are pulled away from vertebral bodies [ 95 , 96 , 97 ]. Nonetheless, since most of the psoas muscle fibers are still preserved in OLIF, it is less associated with hip flexion weakness, with only up to 1.2–13.9% of patients experiencing postoperative hip flexion weakness as compared to 4.9–31.4% in XLIF [ 95 , 96 , 98 , 99 , 100 , 101 , 102 , 103 , 104 ]. As the lumbar plexus is also avoided, there is a reduced likelihood of lower limb sensory and motor weakness following OLIF as compared to XLIF.…”
Section: The Oblique Lumbar Interbody Fusion (Olif)mentioning
confidence: 99%
See 1 more Smart Citation
“…Some nerve branches supplying the psoas traverse the intervertebral disc obliquely prior to ramification within the muscle and are, therefore, vulnerable to injury when muscle fibers of the superficial layer of psoas are pulled away from vertebral bodies [ 95 , 96 , 97 ]. Nonetheless, since most of the psoas muscle fibers are still preserved in OLIF, it is less associated with hip flexion weakness, with only up to 1.2–13.9% of patients experiencing postoperative hip flexion weakness as compared to 4.9–31.4% in XLIF [ 95 , 96 , 98 , 99 , 100 , 101 , 102 , 103 , 104 ]. As the lumbar plexus is also avoided, there is a reduced likelihood of lower limb sensory and motor weakness following OLIF as compared to XLIF.…”
Section: The Oblique Lumbar Interbody Fusion (Olif)mentioning
confidence: 99%
“…Similar to XLIF, OLIF is known to restore sagittal profiles and satisfies Schwab’s criteria for proper global alignment [ 111 ]. Proper global alignment has been linked to improved quality of life for adult patients with spinal deformities, especially spondylolisthesis [ 104 , 112 , 113 , 114 , 115 , 116 , 117 ]. Ko et al measured the sagittal disc angle (SDA), coronal disc angle (CDA), mean disc height (MDH), and intervertebral foramen height (FH) directly after the XLIF and OLIF surgery, and one year postoperatively.…”
Section: The Oblique Lumbar Interbody Fusion (Olif)mentioning
confidence: 99%
“…Fourth, the interbody fusion used in OLIF is much larger compared to conventional posterior fusions, and it is placed across the endplate, which significantly enhances its biomechanical stability. In addition, OLIF has the advantages of a low complication rate, less surgical blood loss, shorter operative time, and shorter patient hospital stay (Mobbs et al, 2015;Aleinik et al, 2021). Joseph et al (2015) reported a complication rate of 20.2% (380/1885) after TLIF, whereas Abe et al ( 2017) reported a complication rate of 1.2% (2/155) after OLIF, indicating a significant reduction in innerve injury with OLIF.…”
Section: Open Accessmentioning
confidence: 99%
“…Oblique lateral lumbar interbody fusion (OLIF) is considered one of the best options for lumbar fusion ( Aleinik et al, 2021 ). In 1997, Mayer ( Mayer, 1997 ) described a minimally invasive anterior approach to the lumbar spine through a retroperitoneal approach at the L2-L5 level and a transabdominal approach at the L5-S1 level, which first proposed OLIF.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, the interbody fusion used in OLIF is much larger compared to conventional posterior fusions, and it is placed across the endplate, which significantly enhances its biomechanical stability. In addition, OLIF has the advantages of a low complication rate, less surgical blood loss, shorter operative time, and shorter patient hospital stay ( Mobbs et al, 2015 ; Lu and Lu, 2019 ; Aleinik et al, 2021 ). Joseph et al (2015) reported a complication rate of 20.2% (380/1885) after TLIF, whereas Abe et al (2017) reported a complication rate of 1.2% (2/155) after OLIF, indicating a significant reduction in innerve injury with OLIF.…”
Section: Introductionmentioning
confidence: 99%